Patriarchal Ideology in Good Wife, a Horror Episode of Korean Webtoon Shriek - Agnes Emmilia Eka Rosanti (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
When the couple of man and woman have become husband and wife, it means that the husband becomes the head of family and father of his children while the wife becomes the breadwinner of the family and mother of her children. However, there is a misconception of the ‘head and breadwinner of the family.’ The misconception is that since the husband is the head of the family, it means the husband can order his wife. While the wife, since she roles as the ‘breadwinner’, she must obey and be submissive to her husband and her in-laws. If something bad happens to the husband, the wife will be blamed, even when the wife gets angry at her husband for some reasons, still the wife is the one to blame.